1992
DOI: 10.1007/bf00198848
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of cell wall proteins of Listeria monocytogenes

Abstract: Two proteins were purified from Listeria monocytogenes cell wall using detergent extraction, Superose 6 gel chromatography. Mono Q cation-exchange chromatography and Superose 12 gel chromatography. Proteins were shown to form complexes of ca. 300 kDa and pI 4.7. These complexes could not be dissociated in 6 M urea, however, during SDS-PAGE 79 and 39 kDa monomers were formed. Immunoblot analysis showed that the proteins under investigation were common to all listerial strains tested, but were absent in strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Our size exclusion data shows that monomeric ActA has a Stokes radius of 8.0 nm (Fig. 2), in agreement with previously published results (32,34). A Stokes radius of 8.0 nm corresponds to a globular protein of 710 kDa.…”
Section: Characterization Of the Soluble Acta Protein And Syntheticsupporting
confidence: 92%
See 1 more Smart Citation
“…Our size exclusion data shows that monomeric ActA has a Stokes radius of 8.0 nm (Fig. 2), in agreement with previously published results (32,34). A Stokes radius of 8.0 nm corresponds to a globular protein of 710 kDa.…”
Section: Characterization Of the Soluble Acta Protein And Syntheticsupporting
confidence: 92%
“…Analytical ultracentrifugation has demonstrated that ActA exists as a monomer in solution (20,32) with ambiguous results regarding higher order multimers (32). ActA has been shown to behave as an anomalously large species by gel filtration, suggesting that it may be an elongated molecule (32,34). Dimer formation has been reported for ActA (35) based on its ability to interact with itself in a yeast two-hybrid assay and on crosslinking in situ on the bacterial surface to a dimeric form but not to higher-order multimers.…”
mentioning
confidence: 99%
“…Next, we examined proteins of cell walls and supernatants of NG602 and the parental strain in Western immunoblotting with antiserums against listeriolysin O, PI‐PLC and metalloprotease. As a control we used a cell wall protein Lm79/39, the expression of which remains constant under conditions affecting virulence protein expression [12]. Elevation of production of PI‐PLC and metalloprotease by NG602 was revealed in supernatant of liquid culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For isolation of cell wall we used the method described earlier [2]. In brief, L. monocytogenes was grown in Brain Heart Infusion Broth (Difco, USA).…”
Section: Isolation Of Cell Wall and Extraction Proceduresmentioning
confidence: 99%
“…In a previous investigation we succeeded in purifying two proteins with molecular masses of 79 and 39 kDa. The proteins were common to all tested listerial strains and, thus, appeared to represent genus-wide markers of the bacterium [2]. The aim of the present study was the further characterization of cell-associated proteins of L. monocytogenes.…”
Section: Introductionmentioning
confidence: 99%